The effects of a commercial purification system on the fluoride content of water - Dealca, Catherine Lovegel M.; Deveza, Mary Frances Celestine S.; Tala, Hazel (Adviser).
The ever increasing threat of water pollution and water-borne diseases has led to the widespread popularity of water purification stores throughout the country. The aim of the study was to determine the effects of a commercial water purification system on the fluoride content of water in Cavite City, Cavite. Nine 350 ml samples from the purification store's raw water source served as control, and another nine 350 ml samples were taken after passage through the purification system. These eighteen water samples were tested for fluoride content in the UP Research and Analytical Services Laboratory using a fluoride ion specific electrode. The control samples had a mean fluoride content of 0.91889 ppm, whereas the fluoride content of all the purified water samples were reduced to less than 0.02 ppm. Analysis of the data was done using the T-test. The reduction in fluoride content after passage through the purification system was found to be statistically significant. Therefore the commercial water purification system used in the study has the ability to significantly reduce the fluoride content of water.
Seminar Paper-Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Water -- Purification -- Philippines; Fluorides